Preliminary experience with 3D digital image microscope system on the treatment of varicocele. (21st March 2022) - Yao, Chencheng; Xu, Wang; Liu, Nachuan; Zhi, Erlei; Shi, Chenkun; Ji, Zhiyong; Zhao, Jingpeng; Tian, Ruhui; Huang, Yuhua; Zhao, Fujun; Chen, Huirong; Zhang, Pei; et al.
Abstract: The three‐dimension digital image microscope system (3D‐DIM) with a better ergonomic design and equipment characteristics can contribute to the achievement of good results during microsurgery. In this study, the safety and efficiency of 3D‐DIM assisted varicocelectomy was evaluated. From July 2019 to November 2019, fifteen cases with varicocele (20 sides of varicocele in total) were included, seven cases underwent 3D‐DIM‐assisted modified microsurgical subinguinal varicocelectomy, and eight cases underwent modified microsurgical subinguinal varicocelectomy under standard operating microscope (SOM). The mean operative time of 3D‐DIM group (67 ± 12.3 min) was a little longer than that of SOM group (55 ± 12.9 min) ( p  < 0.05). There was no significant difference between the two groups in the number of internal spermatic arteries, internal spermatic vein, lymphatics, gubernacular vein, external spermatic vein and post‐operation complications. The 3D‐DIM showed a significant difference in image definition for nurse ( p  < 0.01) and in doctor–nurse cooperation ( p  < 0.05) over SOM. The 3D‐DIM with better ergonomic design and image definition can be applied to perform microsurgical subinguinal varicocelectomy, and could improve the surgeon's fatigue and doctor–nurse cooperation. We believe that the 3D‐DIM would be widely used in the field of male infertility microsurgery in the near future.